Making My Future Work: Evaluation of a New College and Career Readiness Curriculum. Issue 6 (September 2018) - Perry, Justin C.; Wallace, Eric W.; McCormick, Meghan P.
The college and career readiness movement figures prominently in the nation's educational reform and policies, including strategies to increase graduation rates among disadvantaged students in urban schools. As part of a multi-pronged approach to help youth transition to post-secondary education and the workforce, the present study evaluated a new career intervention, Making My Future Work, designed to serve as a comprehensive, flexible career curriculum. Based on a quasi-experimental design among a sample of urban youth ( N = 429), multilevel modeling revealed promising evidence for its impact across a range of outcomes, including grade point average, school engagement, career preparation, self-determination, and self-awareness. The implications of the findings, limitations, and future directions for research are discussed.